PENGEMBAPengembangan LKPD Berbasis Auditory Intellectually Repetition (AIR) untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi pada Pembelajaran IPANGAN LKPD BERBASIS AUDITORY INTELLECTUALLY REPETITION (AIR) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI PADA PEMBELAJARAN IPA - Yusmia Nandini; Juhji Juhji; Asep Saefurohman (Pendagogia: Jurnal Pendidikan Dasar, 2024)
Development of AIR-Based LKPD to Develop Students' Higher Level Thinking Skills. Teaching materials are an important component of learning activities. In fact, the existing teaching materials used by teachers still do not meet students' needs for higher level thinking. The aim of this research is to produce products and describe the effectiveness of Auditory Intellectually Repetition (AIR) based LKPD to improve high level thinking skills as teaching material for learning simple electrical circuits. This LKPD was developed in accordance with systematic and standard criteria for eligibility and testing the effectiveness of learning media. The research carried out is a type of development research using the Analysis, Design, Development, Implementation, Evaluation development model. The process for producing LKPD begins with a validation stage by experts. AIR-based LKPD was also tested in schools to measure the response of class VI students. The results of the research show that the final validation results from media experts are 85% with very feasible criteria, the assessment results by material experts are 94% with very feasible criteria, the assessment results by language experts are 98% with very feasible criteria, the assessment results by the sixth grade teacher at Cimuncang Cilik State Elementary School with a percentage of 95% and the results of the effectiveness test of 15 students, pretest with a percentage of 13.3% and posttest with a percentage of 86%, as well as from the results of the N-Gain calculation, the percentage was 68% with the criteria being quite effective. The student response was 85.6% with very effective criteria, so the AIR-based LKPD was declared valid and practical for use as a reference in the learning process.